Theoretical concepts "land management process", "land management procedure" and their relationships - Tretiak, A.; Dorosh, Y.; Tretiak, R. (Land Management, Cadastre and Land Monitoring, 2017)
The state significance of land management activities is manifested in those legal consequences that arise after the issuance of land management documentation and are conditioned by the need to secure unsupported land rights and the use and protection of land in a state-guaranteed manner. The procedural activity of land surveyors and other persons authorized by the state to commit land management operations must be carried out in a certain order established by the state and obey the rights and obligations of the persons specified by the legislation at each stage of the development of such relations.The main goal of applying to land management organizations and land surveyors is landuse documentation, which is made in accordance with the requirements of the law and with which the relevant legal properties of the land management procedure are associated.First of all, let's dwell on such basic concepts as "land management process" and "land management procedure". Consideration of the term "land management process" implies a preliminary analysis of the category "process". At the same time, it must be admitted that the development of the procedural form of this category has not been paid attention. Considering the concept of "land management process", its place and role in the system of social relations, emphasis will be placed on the concept of a broad understanding of the legal process, the problem of which exists for decades.Thus, the legal process is a regulated by the procedural rules procedure for the activities of competent state bodies, consisting of the preparation, adoption and documentary consolidation of legal decisions of a general and individual nature. In the land law, the category "process" is specific and serves to designate relationships that provide regulatory and security land-property relationships.Particularly difficult today is the question of the delimitation of the concepts of "process" and "procedure" in general. Regarding the land management process, we believe that the land management process is an activity directly related to the need to use different methods and means of legal acts. Elements of the land management process are its subjects, stages and proceedings, which allow to outline the boundaries in space and time and the substantive composition of this form of activity. Many scholars regard the procedure as a broader concept that should absorb the process.The stability of any procedure, including land management, will depend on its perfection, which is determined by the duration of its application or the "test of action". Consequently, if the procedure is a static norm, and procedural activity is its dynamic criterion, then the latter must constantly check the land management procedure for its compliance with its needs of individuals and society.Any procedure should have certain limits. Regarding land management procedures, it should provide legal certainty (veracity) to land-based operations. Consequently, its boundaries should be legislatively enshrined. The action and its regulation by law may differ, indicating the need to compare them as relatively independent legal categoriesin some cases. Thus, for land management science and practice, it is necessary to consolidate two relatively independent concepts of "land management" and "land management procedure", which will distinguish the actual behavior of subjects from the regulated by law.Keywords. Land management, land management process, land management project, land management procedure, land management actions.